Gender as a Moderator of the Relation Between Age Cohort and Three-Dimensional Wisdom in Iranian Culture. (July 2015) - Cheraghi, Fereshte; Kadivar, Parvin; Ardelt, Monika; Asgari, Ali; Farzad, Valiollah
This study examined whether gender moderated the association between age cohort and the cognitive, reflective, and compassionate dimensions of wisdom, using an Iranian sample of 439 adults from three age cohorts: young (18–34), middle-aged (35–54), and older (55 and above). Results indicated that the interaction effect between gender and age cohort was significant for three-dimensional wisdom and all three wisdom dimensions. Compared with younger women and older men, older women tended to have less education and to score lower on the cognitive wisdom dimension, but they had similar average scores as older men on the compassionate wisdom dimension. Overall, the association between age and wisdom was only positive for men, due mainly to the positive relation between age and the reflective and compassionate wisdom dimensions for men after adjusting for education. The results are interpreted with reference to generation gaps, socialization of men versus women, and life experiences and opportunities.